FABA block medium for eucalyptus (Melaleuca cajuputi) seedling planting and acid mine drainage neutralization in artificial wetlands - Alwysihah, Hafid; Mansur, Irdika; Wulandari, Arum Sekar; Siregar , Elisa Weber; Suwondo, Suwondo; Rakhman , Rizali (Journal of Degraded and Mining Lands Management, 2025)
Open-pit coal mining activities have an impact on environmental changes, one of which is the emergence of acid mine drainage. Acid mine drainage (AMD) arises from sulfide minerals that react with oxygen and water. Coal utilized in electric steam power plants as fuel to produce electrical energy results in combustion residue known as fly ash and bottom ash (FABA). FABA has alkaline properties and has the potential to be combined with plant species that are resistant to acid mine drainage (AMD). This study aimed to explore the potential use of FABA as a growing medium for eucalyptus (Melaleuca cajuputi) to neutralize the pH of acid mine drainage (AMD) in artificial wetlands. FABA block medium was made by mixing FABA, cow manure, and cement as an adhesive and incorporating holes as planting media. The results of this study showed that the application of FABA and cow manure increased the pH of AMD from 3.27 to 6.27 in 24 hours. FABA medium blocks could adsorb heavy metals in AMD, such as Fe in the K1-P1 treatment, from a value of 0.15 mg/L to 0.08 mg/L, and heavy metal Mn in the K3-P3 treatment, from a value of 4.1 mg/L to 0.2 mg/L. In addition, medium blocks K2 (50% FABA + 30% cow manure + 20% cement) and K3 (30% FABA + 50% cow manure + 20% cement) had a good effect on the growth of M. cajuputi seedlings in the K3-P1 treatment with an average height of 17.67 cm and a stem diameter of 9.2 mm for 8 weeks.